(3CNHGQ GdLfs - (3jhSa, YUGes ((3GdLjRI, eUQs (3GdYGdejI ddcJH hGdfTQs, 2010)
(3GdcJGH jJfGhd ehVhY GdLf hCfhGYg hYdGbI GdEfSGf HbQjfg hcja jbi GdEfSGf faSg ef NWQ GdLf hcja cGf jYGdL GdQShd GdcQje GdSMQ ceG jJfGhd GdcJGH MhGQ GdCfHjGA hGdUMGHI eY GdLfs
(3GdeMJhjGJ (B: (3eG gh GdLf(B--(3COdI hLhO GdLf(B--(3CfhGY GdLf(B--(3GdbQjf hYdGbJg HdEfSGf(B--(3ai CMhGd GdLf(B--(3YdGL GdeUQhY ef cJGH GdWH GdfHhis
(3jTJed Ydi bGFeI HGdeQGLY ai fgGjI GdcJGHs
(3jTJed Ydi bGFeI HGdeQGLY eNJUQI ai HYV GdUaMGJs
Hurg
5
Keywords: (3GdJYGhjPs; (3GdLfs; (3GdNQGaGJs; (3GdSMQs; (3GdTjGWjf hGdLGfs; (3GdWdGSe GdSMQjIs; (3GdYdGL GdOjfis; (3GdYdGL HGdbQBfs; (3Gdbhi GdNajIs